Reportaż podróżniczy w czasach antycznych i współczesnych, czyli śladami Herodota i Kapuścińskiego - Gryksa, Edyta (Colloquia Litteraria, 2023)
The aim of the article is to compare the reporter’s skills of Herodotus – the father of history – and Ryszard Kapuściński – the legend of world literature. The main emphasis is placed on issues related to the oral tradition of the acquired messages, literary workshop, travel metaphor and a brief description of the Histories and The Journeys with Herodotus.